2010
DOI: 10.1088/1741-2560/7/1/016002
|View full text |Cite
|
Sign up to set email alerts
|

In vivoelectrochemical characterization and inflammatory response of multiwalled carbon nanotube-based electrodes in rat hippocampus

Abstract: Stimulating neural electrodes are required to deliver charge to an environment that presents itself as hostile. The electrodes need to maintain their electrical characteristics (charge and impedance) in vivo for a proper functioning of neural prostheses. Here we design implantable multi-walled carbon nanotubes coating for stainless steel substrate electrodes, targeted at wide frequency stimulation of deep brain structures. In well-controlled, low-frequency stimulation acute experiments, we show that multi-wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Tracking of inflammatory response in vivo is of importance if the objective of the implant is charge transfer. We have demonstrated that certain inflammatory molecules, initially active at the electrode-nervous tissue interface, do not prevent charge transfer neither increase the impedance of MWCNT electrodes in acute implants (Minnikanti et al, 2010). This effect of molecular interaction occurring at the interface of MWCNTs and neural tissue needs to be further investigated.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Tracking of inflammatory response in vivo is of importance if the objective of the implant is charge transfer. We have demonstrated that certain inflammatory molecules, initially active at the electrode-nervous tissue interface, do not prevent charge transfer neither increase the impedance of MWCNT electrodes in acute implants (Minnikanti et al, 2010). This effect of molecular interaction occurring at the interface of MWCNTs and neural tissue needs to be further investigated.…”
Section: Discussionmentioning
confidence: 91%
“…However, stability of conductive polymers is questionable (Ansaldo et al, 2011;Peixoto et al, 2009). CNTs, with their distinctive properties, can improve the performance of NE, as a coating over the metallic electrodes (Minnikanti et al, 2010) or when electrochemically co-deposited with conductive polymers (Keefer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations